2020
DOI: 10.1504/ijatm.2020.105297
|View full text |Cite
|
Sign up to set email alerts
|

Is more automation always better An empirical study of customers' willingness to use autonomous vehicle functions

Abstract: Sometime, many (maybe all) vehicles on our streets will drive autonomously -or at least have autonomous functions. However, in the short run, consumers' preferences regarding the automation of pivotal vehicle functions are not entirely clear. This paper accordingly investigates consumers' willingness to use three levels of automation (none, partial, and full) of potentially autonomous vehicle functions (safety, parking prediction, and remote diagnostics). The results show that consumers' willingness to use aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 19 publications
(29 reference statements)
1
4
0
Order By: Relevance
“…For purchase intentions, positive relationships can be seen between reliability (r = 0.431, p < 0.01), safety (r = 0.400, p < 0.01) and service provider attributes (r = 0.396, p < 0.01). The findings reinforced the importance of reliability and safety attributes of autonomous vehicles and their relationships with customer purchase intentions (Merfeld, 2019;Schmalfuß et al, 2017;Souka et al, 2019). The strongest correlation is seen between customer perceived value and purchase intentions (r = 0.499, p < 0.01), which provided support for H6.…”
Section: Resultssupporting
confidence: 59%
See 2 more Smart Citations
“…For purchase intentions, positive relationships can be seen between reliability (r = 0.431, p < 0.01), safety (r = 0.400, p < 0.01) and service provider attributes (r = 0.396, p < 0.01). The findings reinforced the importance of reliability and safety attributes of autonomous vehicles and their relationships with customer purchase intentions (Merfeld, 2019;Schmalfuß et al, 2017;Souka et al, 2019). The strongest correlation is seen between customer perceived value and purchase intentions (r = 0.499, p < 0.01), which provided support for H6.…”
Section: Resultssupporting
confidence: 59%
“…In a study on electric vehicles in a shared autonomous vehicle setting, Schmalfuß et al (2017) found the importance of riders' perceptions of safety and reliability in autonomous vehicle operations. Similarly, safety was found to be the most important factor in studies on autonomous vehicle functions (Souka et al, 2019) and autonomous vehicle sharing (Merfeld et al, 2019), while Panagiotopoulos and Dimitrakopoulos (2018) found that safety concerns towards autonomous vehicles can have a negative influence on the intention to use and adopt the vehicles.…”
Section: Safety and Reliabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Diverse factors may be important for potential AV users. While some studies [9] [15] have emphasized the importance of the level of control a driver has over the vehicle, others [16] [17] have emphasized the vehicle's ability to flawlessly navigate and maneuver on its own. Although it has been predicted by some [2] that AVs will be safer because they will eliminate human error, for AV non-users, especially vulnerable road users like pedestrians, bicyclists, and people with disabilities, having to share roads with vehicles with unfamiliar or vaguely familiar technologies can be a reason for extreme safety concern.…”
Section: Relevant Literaturementioning
confidence: 99%
“…Consequently, novel research questions, for example, with respect to additional or possibly different drivers and barriers of product adoption emerge (Mani and Chouk 2018 ; Schweitzer and van den Hende 2016 ; Souka et al. 2020 ). The effect of the anthropomorphism of a smart product on purchase intention may serve as an illustrative example.…”
mentioning
confidence: 99%